EFFECTIVENESS OF PUPPETRY ON CONCEPT FORMATION AMONG STUDENTS WITH MODERATE INTELLECTUAL DISABILITY - Arun M, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study under investigation is an experimental one which aims to find out the effectiveness of Puppetry on Concept Formation among students with moderate level of Intellectual Disability. Pre-test-Post-test Non Equivalent Groups Design was used for the study. For this purpose a sample of 12 students were drawn from a special school. Purposive sampling was used for the selection of sample. Students with mild intellectual disability were the sample of the study where 6 students were in the experimental group and 6 students in the Control group. The experimental group students were using Puppetry method. The control group students were taught through the existing method of teaching used for students with Intellectual Disability. For the analysis of the collected data the investigator used descriptive statistics like Mean, median, mode, standard deviation and Mean Difference Analysis. The study reveals that there exists significant difference between post test scores of Experimental and Control group with respect to Concept formation. Students in the experimental group show significantly better performance in terms of concept formation than students in the Control group as higher mean scores are attached with them.